Association among plasma 1, 25(OH)2D, ratio of 1, 25(OH)2D to 25(OH)D, and prostate cancer aggressiveness. Issue 10 (11th May 2019) - Ramakrishnan, Swathi; Steck, Susan E.; Arab, Lenore; Zhang, Hongmei; Bensen, Jeannette T.; Fontham, Elizabeth T. H.; Johnson, Candace S.; Mohler, James L.; Smith, Gary J.; Su, L. Joseph; Woloszynska, Anna
Abstract: Background: African‐American (AA) men tend to present with more aggressive prostate cancer (Gleason score >7) than European‐American (EA) men. Vitamin D and its metabolites are implicated in prostate cancer biology with vitamin D deficiency, indicated by its metabolite levels in serum or plasma, usually observed in AA men. Objective: To determine if 1, 25‐dihydroxy vitamin D3 [1, 25(OH)2 D] plasma levels in AA and EA prostate cancer patients alter the risk of having aggressive prostate cancer. Design: Research subjects from the North Carolina‐Louisiana Prostate Cancer Project (AA n = 435 and EA n = 532) were included. Plasma metabolites 1, 25(OH)2 D and 25‐hydroxyvitamin D3 [25(OH)D] were measured using liquid chromatography with tandem mass spectrophotometry. Research subjects were classified into low (Gleason sum < 7, stage T1‐T2, and Prostate‐specific antigen (PSA) < 9 ng/mL) or high (Gleason sum > 8 or Gleason sum = 7 with 4 + 3, or PSA > 20 ng/mL, or Gleason sum = 7 and stage T3‐T4) aggressive disease. Results: Research subjects in the second and third tertiles of plasma levels of 1, 25(OH)2 D had lower odds of high aggressive prostate cancer (AA [ORT2vsT1 : 0.66, 95%CI: 0.39‐1.12; ORT3vsT1 : 0.83, 95%CI: 0.49‐1.41] and EA [ORT2vsT1 : 0.68, 95%CI: 0.41‐1.11; ORT3vsT1 : 0.67, 95%CI: 0.40‐1.11]) compared with the first tertile, though confidence intervals included the null. Greater 1, 25(OH)2 D/25(OH)D molar ratios were associated with lower odds of high aggressive prostate cancer more evidently in AA (ORQ4vsQ1 : 0.45, CI: 0.24‐0.82) than in EA (ORQ4vsQ1 : 0.64, CI: 0.35‐1.17) research subjects. Conclusions: The 1, 25(OH)2 D/25(OH)D molar ratio was associated with decreased risk of high aggressive prostate cancer in AA men, and possibly in EA men. Further studies analyzing vitamin D polymorphisms, vitamin D binding protein levels, and prostatic levels of these metabolites may be useful. These studies may provide a better understanding of the vitamin D pathway and its biological role underlying health disparities in prostate cancer.